УЛС ТӨРИЙН МАРКЕТИНГИЙН ТУХАЙ ОНОЛЫН ХУРААНГУЙ - С.Базарпүрэв; Б.Нандин-Эрдэнэ (Politology, 2023)
As political marketing has been going into independent science, numeral research subject have continuously emerged. This study examined a literature review of the political marketing science